Developing a Deep Learning Framework in Islamic Education for Student Graduate Competencies - Karlina; Yahdinil Firda Nadirah; Deni Iriyadi; Wasehudin; Fitri Hilmiyati (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study addresses a critical gap in Islamic Religious Education (IRE), where existing pedagogical practices remain predominantly transmission-oriented and insufficiently integrate contemporary deep learning frameworks within an اسلامی epistemological paradigm. While deep learning has been widely discussed in modern educational discourse, its conceptual reconstruction based on Islamic values—particularly in relation to tazkiyat al-nafs, adab, and holistic human development—remains underexplored. Accordingly, this study aims to analyze how deep learning can be theoretically and pedagogically integrated into IRE to strengthen students’ graduate profiles. Using a qualitative literature review approach, this study synthesizes contemporary educational theories with classical Islamic scholarship to develop a conceptual framework that bridges cognitive, affective, and spiritual dimensions of learning. The findings demonstrate that deep learning in IRE can be reconstructed through three interrelated principles: mindful learning (linked to muraqabah and self-awareness), meaningful learning (connected to hikmah and contextual understanding), and joyful learning (aligned with targhib and intrinsic motivation). From an operational perspective, outcomes such as creativity, collaboration, and independence are reflected through indicators including students’ problem-solving abilities, participation in cooperative learning tasks, and self-regulated learning behaviours, as identified across the reviewed literature. The study contributes by offering both an epistemological and pedagogical model of deep learning grounded in Islamic values, thereby extending current discourse beyond technical implementation toward value-based educational transformation. This model provides a conceptual foundation for developing IRE practices that are not only cognitively rigorous but also spiritually meaningful and socially relevant.